Apexification in a mandibular first molar with a middle mesial canal - Quiñones Pedraza, Jesús Alejandro (Clin Case Rep, 2018)
Apexification procedures have been widely used to treat teeth with incomplete root development and pulp necrosis. The middle mesial canal (MMC) is an anatomical variation and in most cases represents a challenge during endodontic treatments. In this article, a favorable outcome is reported after apexification in a molar with MMC.